Aligned MHD of Ferrofluids with Convective Boundary Condition past an Inclined Plate - Rijal Ilias, Mohd; Afiqah Rawi, Noraihan; Sa’aidah Ismail, Nur; Shafie, Sharidan (International Journal of Engineering and Technology, 2018)
The numerical investigation is carried out for the MHD free convection laminar boundary layer flow that allows heat transfer of an elec-trically conducting Fe3O4–kerosene and Fe3O4–water-based ferrofluids. For this, an inclined plate is employed that has aligned effect as well as transverse magnetic field effect. Suitable similarity transformations are used to convert governing partial differential equations into a coupled nonlinear ordinary differential equation. The Keller Box method, a well-known explicit finite difference scheme is then employed to solve transformed equations numerically. For different values of physical parameters, a detailed parametric study is conducted. Means of graphs are extrapolated to determine the effects of all these parameters over temperature and the flow field. For various values of physical parameters, the numerical values are obtained and tabulated for skin friction coefficient and the rate of heat transfer as well. Comparisons with previously published work are performed and excellent agreement is obtained.